Effects of the sigma-1 receptor agonist blarcamesine in a murine model of fragile X syndrome: neurobehavioral phenotypes and receptor occupancy - Samantha T. Reyes (Nature Portfolio, 2021)
Abstract Fragile X syndrome (FXS), a disorder of synaptic development and function, is the most prevalent genetic form of intellectual disability and autism spectrum disorder. FXS mouse models display clinically-relevant phenotypes, such as increased anxiety and hyperactivity. Despite their availability, so far advances in drug development have not yielded new treatments. Therefore, testing novel drugs that can ameliorate FXS’ cognitive and behavioral impairments is imperative. ANAVEX2-73 (blarcamesine) is a sigma-1 receptor (S1R) agonist with a strong safety record and preliminary efficacy evidence in patients with Alzheimer’s disease and Rett syndrome, other synaptic neurodegenerative and neurodevelopmental disorders. S1R’s role in calcium homeostasis and mitochondrial function, cellular functions related to synaptic function, makes blarcamesine a potential drug candidate for FXS. Administration of blarcamesine in 2-month-old FXS and wild type mice for 2 weeks led to normalization in two key neurobehavioral phenotypes: open field test (hyperactivity) and contextual fear conditioning (associative learning). Furthermore, there was improvement in marble-burying (anxiety, perseverative behavior). It also restored levels of BDNF, a converging point of many synaptic regulators, in the hippocampus. Positron emission tomography (PET) and ex vivo autoradiographic studies, using the highly selective S1R PET ligand [18F]FTC-146, demonstrated the drug’s dose-dependent receptor occupancy. Subsequent analyses also showed a wide but variable brain regional distribution of S1Rs, which was preserved in FXS mice. Altogether, these neurobehavioral, biochemical, and imaging data demonstrates doses that yield measurable receptor occupancy are effective for improving the synaptic and behavioral phenotype in FXS mice. The present findings support the viability of S1R as a therapeutic target in FXS, and the clinical potential of blarcamesine in FXS and other neurodevelopmental disorders.